Long-term Magnetic Resonance Imaging Follow-up of Asymptomatic Sellar Tumors —Their Natural History and Surgical Indications - SAEKI, Naokatsu; YAMAURA, Akira; IGARASHI, Takuji (Neurologia medico-chirurgica, 1999)
Serial magnetic resonance (MR) images and clinical symptoms were analyzed in 23 patients with sellar lesions, who were followed up without initial therapy for mass reduction to evaluate their natural history and surgical indication for these lesions. The patients were aged 17 to 78 years (mean 47.3 years) and the follow-up period was 1.5 to 11.6 years (mean 5.1 years). Lesions were divided into two types based on the MR imaging findings, regardless of their histological types. Type C was cystic with or without enhancement of the smooth and thin wall. Type S had enhanced solid components. Ten patients had Type C tumors. Three patients presented with sudden onset of headache. The tumor size spontaneously decreased with intensity change, indicating pituitary apoplexy as the trigger of the onset and intensity change. Four patients presented with the visual disturbance which improved with the reduction of tumor size, but three patients deteriorated and required surgery. The operation revealed Rathke''s cleft cyst. The remaining three patients were found incidentally and have been asymptomatic without MR imaging changes. Thirteen patients had Type S tumors. Six patients of nine with 14 mm or larger tumors developed symptomatic tumor enlargement over the follow-up period of 1.2 to 8.6 years (mean 4.9 years) and required treatment. The remainder showed no change. Type C tumors frequently shrink or even disappear spontaneously. We can justify conservative follow-up of Type C tumors in patients with no or only transient symptoms. Type S tumors, larger than 14 mm in size, need closer observation or treatment because they often enlarge and become symptomatic.